Odpowiedzi

2010-03-28T23:28:54+02:00
2(X-½)-x+3=3
2x-1-x+3=3
x=3-2
x=1

3(1-x)-(1-2x)=9
3-3x-1+2x=9
-x= 9-7
-x=2 |*(-1)
x=-2

0=3-(2x+1)
0=3-2x-1
-2x=-3+1
-2x=-2 |:(-2)
x=1

0,5(2-4x)=3-x
1-2x=3-x
-2x+x=3-1
-x=2 |*(-1)
x=-2

12y-(y+5)=10y-1
12y-y-5=10y-1
11y-10y=-1+5
y=4

2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10
2u+5=3u-2
-u=-7 |*(-1)
u=7

2x-½(3x-2)=7/4-x |*4
8x-6x+4=7-4x
2x+4x=7-4
6x=3|:6
x=½

3⅓x+8=4 ⅖x-8
3⅓x-4⅖x=-8-8
3⁵/₁₅x-4⁶/₁₅x=-16
⁵⁰/₁₅x-⁶⁶/₁₅x=-16
-¹⁶/₁₅x = -16 |*(-¹⁵/₁₆)
x=15

(-½x+1)+3x/2=3
-½x+1+3x/2=3 |*2
-x+2+3x=6
2x=4 |:2
x=2
Najlepsza Odpowiedź!
2010-03-28T23:31:17+02:00
2(X-½)-x+3=3
2x-1-x+3=3
x=3-2
x=1

3(1-x)-(1-2x)=9
3-3x-1+2x=9
-x=9-2
-x=7
x=-7

0=3-(2x+1)
0=3-2x-1
2x=2
x=1

0,5(2-4x)=3-x
1-2x=3-x
-2x+x=3-1
-x=2
x=-2

12y-(y+5)=10y-1
12y-y-5=10y-1
12y-y-10y=-1+5
y=4

2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10
2u-3u=-2-5
-u=-7
u=7

2x-½(3x-2)=7/4-x
2x-1½+1=7/4-x /*4
8x-6x+4=7-4x
2x+4x=7-4
6x=3
x=1/2

3⅓x+8=4 i 2/5x-8
10/3 x+8=22/5 x-8 /*15
50x+120=66x-120
50x-66x=-120-120
-16x=-240
x=15

(-½x+1)+3x/2=3 /*2
-x+2+3x=6
2x=4
x=2
1 5 1